Fiscal policy options in light of recent IMF research - Mark Le Gros Allen (Center for Social and Economic Research (CASE), 2011)
The financial crisis and recession have left a legacy of unusually large fiscal deficits and growing sovereign debt levels in most advanced economies. The paper uses recent research from the IMF to throw light on two questions: how much fiscal space is available to advanced countries before they will be compelled to tighten fiscal policy; and how likely are some countries in this group to default? The paper presents work of Ostry et al. which defines and measures fiscal space. Fiscal space is defined as the room the government has to borrow before it hits a debt limit, the level of debt to GDP at which the debt dynamics become unstable, unless the government undertakes exceptional fiscal action. The debt limit is a function of the past behaviour of the government in responding to fiscal deficits, and fiscal space depends both on the past policy record as well as the current level of debt. The analysis indicates that all advanced countries except Greece, Japan, Portugal and Spain, probably still have some fiscal space. On the likelihood of default, the paper presents work by Cottarelli et al. The paper concludes that the amount of fiscal adjustment needed to avert unsustainable debt dynamics for a number of countries, while large, is not unprecedented, and in any case would not be much reduced by default. The high spreads that have appeared on sovereign debt markets are a poor indicator of subsequent default. And the structure of debt makes default much less likely than in the cases of those (predominantly emerging markets) that have defaulted in the recent past.
Keywords: F34; H60; H62; H63; 330; fiscal sustainability; debt dynamics; advanced economies; fiscal adjustment; public debt; Finanzpolitik; Öffentliche Schulden; Haushaltsdefizit; Haushaltskonsolidierung; Industrieländer